DESAIN APLIKASI KAMUS ISTILAH KOMPUTER BERBASIS ANDROID - Dahlan Susilo; Astri Charolina (Universitas Sahid Surakarta, 2015)
Information and Communication Technology (ICT) is one of the subjects is be taught in SMA. These subjects are learning about computer basic operations, computersoftware, computer hardware, CorelDraw graphic design, internet introduction, computer networks etc. In ICT subjects students use the package book as a learningsupport, in the book there are many computer terms in it. The many existing computer terms make some students have difficulty to understanding the subjects matter, because not all the computer terms are described in the package book.The purpose of this research is to design the dictionary applications of computer terms based Android. The design of application system using UML (Unified ModelingLanguage). The research object in SMA Muhammadiyah 4 Kartasura. The dictionary applicationsdesign of computer term have generated consists of formain menu that is a list menu of terms, menu of guide, menu of about, and menu ofschool profiles are user friendly and very helpful to students in studying ICT subjects.